2009
DOI: 10.1093/eurjhf/hfn037
|View full text |Cite
|
Sign up to set email alerts
|

The cyclic guanosine monophosphate/B‐type natriuretic peptide ratio and mortality in advanced heart failure

Abstract: AimsAttenuation of the effects of natriuretic peptides has been demonstrated in animal models but studies in humans are scarce, particularly concerning renal attenuation. We investigated the attenuation of B-type natriuretic peptide (BNP) in chronic advanced heart failure (HF). Methods and resultsWe included 62 outpatients with HF and severe left ventricular systolic dysfunction. Cases had at least one hospital admission or emergency department visit for acute HF in the previous year and were in NYHA class III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
(48 reference statements)
2
12
0
Order By: Relevance
“…A commercially available multi‐species cGMP EIA measurement kit5 was validated for use in this dog group by confirming intra‐assay precision (coefficient of variation <10%), dilution linearity, and spike recovery in pooled canine plasma. cGMP was measured in plasma for each of the 51 samples in duplicate by spectrophotometry and standard curve methodology as previously described 22. Samples with >10% coefficient of variation were repeated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A commercially available multi‐species cGMP EIA measurement kit5 was validated for use in this dog group by confirming intra‐assay precision (coefficient of variation <10%), dilution linearity, and spike recovery in pooled canine plasma. cGMP was measured in plasma for each of the 51 samples in duplicate by spectrophotometry and standard curve methodology as previously described 22. Samples with >10% coefficient of variation were repeated.…”
Section: Methodsmentioning
confidence: 99%
“…cGMP was measured in plasma for each of the 51 samples in duplicate by spectrophotometry and standard curve methodology as previously described. 22 Samples with >10% coefficient of variation were repeated. cGMP concentrations were separated by genotype as either wild type (matching the canine reference sequence) or polymorphic (either positive heterozygous or positive homozygous for the polymorphism).…”
Section: Methodsmentioning
confidence: 99%
“…The up‐regulation of BNP in response to overload is protective and considered to be a potential therapeutic tool in the treatment of heart failure (HF) . However in HF patients, the beneficial effects of BNP are not always apparent . The reason is multifactorial but may be explained in part by the presence of several BNP molecular entities in blood, each with different biological effects ,.…”
Section: Introductionmentioning
confidence: 99%
“…1 However in HF patients, the beneficial effects of BNP are not always apparent. 2 The reason is multifactorial but may be explained in part by the presence of several BNP molecular entities in blood, each with different biological effects. 3,4 Obviously, knowing how to modulate the formation of truncated BNP may have an impact on the therapeutic approach to patients with HF.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was suggested that dephosphorylation of the NPR-A receptor could potentially play a role in the renal hyporesponsiveness seen in HF patients (Lourenço et al 2009). However, a closer look suggested that in addition to a reduction in NPR-A protein there may also be a reduction in phosphorylated NPR-A protein in the kidney membranes of HF animals .…”
Section: Mechanisms Of Renal Hyporesponsiveness To Bnp In Heart Failurementioning
confidence: 99%